Factors associated with smoking behaviour among Indonesian students: Analysis of the 2019 Global Youth Tobacco Survey - Faisal, Debri Rizki; Putra, Onetusfifsi; Nadira, Nindy Audia (Public Health and Preventive Medicine Archive, 2022)
Background and purpose: The smoking prevalence in youths aged 10-18 years in Indonesia increased from 7.2% in 2013 to 9.1% in 2018. The aim of this study was to assess factors related to smoking behavior among students in Indonesia. Methods: This is a secondary analysis of the 2019 Global Youth Tobacco Survey (GYTS) Indonesia data. The sampling technique used was two-stage cluster sampling, classified by schools and classes. The samples included in this analysis were all students aged 13-15 years who participated in the survey and have complete data, accounted for 9,789 respondents. The data were analysed with the Chi-Square Test and Logistic Regression with a 95% confidence interval and p value of 0.05. Results:  A total of 3,595 students (36.72%) had smoked. The number of respondents was the most in the age group of 13-15 years (51.43%). The number of male respondents was 44.01% and women 55.99%. Most students (90.29%) had seen cigarette advertisements, 55.88% of them saw people smoking in school areas and 46.88% saw teachers smoking at schools. The results of a multivariate analysis found factors affected smoking behaviour in students were the friend's offer to smoke (AOR=10.69; 95%CI: 7.37-15.50), male gender (AOR=13.94; 95%CI: 11.56–16.81) and presence of people smoking in the house (AOR=2.15; 95%CI: 1.88-2.45). Conclusion: Environmental cues and peer pressure are associated with smoking among students. Optimizing smoke free and health education about the dangers of cigarettes is essential to counteract the extensive exposure to environmental influence to smoking.